The euphemism translation technique used in English-Indonesian translation of RPG video game (A case study of Hoyoverse's Honkai Star Rail) - Mustofa, Naufal Arik; Sulistyani, Ummi Nur Laila (Universitas Negeri Semarang, 2025)
Euphemisms serve as essential linguistic tools for navigating social norms and cultural sensitivities. Nonetheless, their use in the realm of video game localization is still a largely unexplored topic, especially regarding the English-Indonesian context. This research examines the translation techniques used for euphemistic phrases in HoYoverse’s Honkai Star Rail, emphasizing both understatement and overstatement euphemisms. A qualitative descriptive method was utilized to gather corresponding English-Indonesian text pairs from the dialogues in the Penacony Trailblaze Mission of the game. These pairs were subsequently examined using the framework of the translation technique proposed by Molina and Hurtado Albir. The examination produced 19 euphemistic phrases, comprising 16 understatements and 3 overstatements. Three translation techniques were identified in total: literal translation (84.2%), amplification (10.5%), and modulation (5.3%). The common use of literal translation indicates that euphemistic techniques used in English and Indonesian in the realm of fantasy RPGs show cross-cultural alignment. The strategic use of modulation, illustrated by translating “crime scene” to “TKP” (Tempat Kejadian Perkara), shows a refined cultural adjustment. The results suggest that significant cultural adaptation might not be essential for successful euphemism translation in gaming situations when the source and target cultures have comparable norms for indirect communication. This study substantially enhances video game localization theory by offering a framework for examining euphemistic elements in interactive narratives. Moreover, it provides useful advice for localization experts dealing with English-Indonesian language pairs.